A rare case of oligodontia - MLV Prabhuji; Shaeesta Khaleel B Ahmed; K Raghunatha; Vijeev Vasudevan; R Murali; D Devaraju (Journal of Indian Academy of Oral Medicine and Radiology, 2012)
Agenesis of permanent teeth is a congenital abnormality where some of the teeth are missing as the follicles needed for the growth of the teeth are completely absent. Documental evidence of this condition is very limited in literature and the etiology is still obscure. The present article highlights a clinical case of oligodontia without any association of systemic condition or syndrome.